(3GdOQQ GdcGefI aj CYjGf GdeGFI GdKGefIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s ((3TeS GdOjf GdSNGhi s)
(3ChdgG (B:s
(3CeG HYO agPG JYdjb ebjO ajg JQGLe ef cGf ai GdeGFI GdKGefI ef GdgLQI GdfHhjI ef GHJOGA SfI EMOi hSHYeGFg Edi BNQ SfI KeGfeGFg ef GdBYjGf hGdYdeGA hGdedhc hGdCeQGA hGdcJGH hGdCOHGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B147 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajg HMjOQ CHGO HGdgfO (B((3QLGd (B283) s
Keywords: (3GdJGQjNs